C–H Bond Functionalization & Synthesis in the 21st Century: A Brief History and Prospectus - White, M. Christina (Synlett, 2012)
Among the frontier challenges facing synthetic chemistry in the 21st century are the interconnected goals of increasing control of chemical reactivity and synthesizing complex molecules with higher levels of efficiency. Catalytic C–H bond functionalization reactions are increasingly being discovered that meet the criterion for useful reactivity (i.e. preparative, predictably selective, and general). Consequently, such reactions are enabling chemists to exploit strategies for complex molecule synthesis and derivatization previously accessible only in nature. This preface highlights some of the achievements and important challenges that remain in the area of C–H bond functionalization.
Keywords: C–H activation; site-selective oxidation; bio-inspired methods; synthetic efficiency; complex molecule synthesis